The Effect Of Work Culture, Compensation And Work Loyalty On Employee Performance With Job Satisfaction As An Intervening Variable Of Rentha Jaya Anugrah Savings And Loan Cooperative - Glovenry Meiwentyr Sinaga; Maman Suratman (Journal Research of Social Science, Economics, and Management, 2025)
This study aims to analyze the influence of work culture, compensation, and work loyalty on employee performance at Koperasi Simpan Pinjam Rentha Jaya Anugrah, with job satisfaction as a mediating variable. A quantitative approach was used with a survey method via a questionnaire. Data was analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to test the direct and indirect relationships between variables. The overall conditions of work culture, compensation, loyalty, performance, and employee satisfaction at Koperasi Simpan Pinjam Rentha Jaya Anugrah were found to be in the Good category, reflecting a relatively healthy and productive work environment. The research findings show that work culture has no direct effect on employee performance, and job satisfaction cannot mediate this relationship. Similarly, compensation does not directly affect employee performance, even when mediated by job satisfaction. On the other hand, work loyalty has a significant positive effect on employee performance. Work loyalty also proved to have a positive effect on employee performance through the mediation of job satisfaction. Additionally, it was found that job satisfaction directly has a positive effect on employee performance. The conclusion of this study is that although work culture and compensation are at a good level, they do not directly influence employee performance. In contrast, loyalty and job satisfaction play a crucial role in improving employee performance at Koperasi Simpan Pinjam Rentha Jaya Anugrah.